Komparasi Kinerja Integrated Development Environment (IDE) Dalam Mengeksekusi Perintah Python - Ismail Setiawan (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2022)
An IDE is basically a software package consisting of tools used to develop and test software. IDEs help automate developer tasks by reducing manual effort and combining all tools in a common framework. If the IDE does not exist, then the developer will have to do the selection, integration, and deployment process manually. This study tries to compare the performance of ideas in recognizing writing errors or the simplest syntax in the python language, namely indentation. The test results of the 6 IDEs used found 1 IDE that managed to detect syntax writing errors, namely w3schools. The choice lies with the developer. Generally, the idea is used for programs such as compiled languages such as C, C++, Java, .NET. While the code editor is used for scripts and interpreted, such as PHP, JavaScript, Python, Ruby. In terms of features, of course, using an IDE is more complete than a text editor. If the developer uses VS code, the environment can be adjusted like a code editor but still carries the reliability of an IDE.